2019
DOI: 10.1016/j.surg.2019.06.006
|View full text |Cite
|
Sign up to set email alerts
|

The effect of gender on operative autonomy in general surgery residents

Abstract: Background: Despite an increasing number of women in the field of surgery, bias regarding cognitive or technical ability may continue to affect the experience of female trainees differently than their male counterparts. This study examines the differences in the degree of operative autonomy given to female compared with male general surgery trainees. Methods: A smartphone app was used to collect evaluations of operative autonomy measured using the 4-point Zwisch scale, which describes defined steps in the prog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
96
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(100 citation statements)
references
References 21 publications
3
96
1
Order By: Relevance
“…49 The explanation could stem from differences in societal upbringing or implicit gender bias, as we have previously discussed. Regardless of the reasons, the persistent gap in self-promotion has a definite impact on women in leadership and can translate into less autonomy in the operating room, 35,50,51 a decreased likelihood of applying for promotions, and less meaningful recommendations when they do apply for those opportunities. 44,52 Women must recognize that they can be their toughest critic and thus remind themselves to be confident and take full advantage of all opportunities.…”
Section: Promotion Criteriamentioning
confidence: 99%
“…49 The explanation could stem from differences in societal upbringing or implicit gender bias, as we have previously discussed. Regardless of the reasons, the persistent gap in self-promotion has a definite impact on women in leadership and can translate into less autonomy in the operating room, 35,50,51 a decreased likelihood of applying for promotions, and less meaningful recommendations when they do apply for those opportunities. 44,52 Women must recognize that they can be their toughest critic and thus remind themselves to be confident and take full advantage of all opportunities.…”
Section: Promotion Criteriamentioning
confidence: 99%
“…Previous studies have for the most part been conducted in a North American training system, in which most findings point to a systemic bias against female residents in training [ 7 , 19 21 ]. While a perceived bias of skills may be present in medical students, a systematic review found no difference in skills acquisition between gender in surgical residents [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, being one of the largest units in general surgery in the country with a high volume of general surgery procedures and number of trainees, we believe the findings to be of wider interest and applicability. It also serves as a balanced report to the ongoing gender equity and disparity debates [ 3 , 7 , 11 , 33 35 ]. In the current study, we report how female residents in general surgery perceive their performance for an entry-level procedure such as laparoscopic appendectomy.…”
Section: Discussionmentioning
confidence: 99%
“…Meyerson et al. showed that even when controlling for level of training and procedural difficulty, female residents still receive less operative autonomy than their male counterparts . Social processes affect our written feedback to trainees and Isaac et al.…”
mentioning
confidence: 96%
“…13 Meyerson et al showed that even when controlling for level of training and procedural difficulty, female residents still receive less operative autonomy than their male counterparts. 16 Social processes affect our written feedback to trainees and Isaac et al showed that evaluations of female medical students' performance were more likely to contain 'tentative' words. 17,18 How do these barriers affect learner confidence and opportunities for growth?…”
mentioning
confidence: 99%